Stay alive - Bell, William Brent; Matthew, Bell.; Hollywood Pictures Home Entertainment (Firm).; Buena Vista Home Entertainment (Firm).; Magna Vision (Burbank, Calif. Hollywood Pictures Home Entertainment Distributed by Buena Vista Home Entertainment ; distributed in the Philippines by MagnaVision, 2006)
After their friend is brutally murdered, a group of friends find themselves in possession of a video-game called "Stay Alive." The game is based on a blood-curdling true story of a 17th century noblewoman who was known as the Blood Countess. Knowing that they should not play with the game, the friends play anyway and realize that once they die in the game, they die for real. As their numbers begin dropping and as they begin dying in the ways they died in the game, the remaining friends realize they must defeat the Blood Countess or accept their deadly fates.
Director of photography, Alejandro Martinez ; editors, Harvey Rosenstock, Mark Stevens ; music, John Frizzell ; costume designer, Caroline Eselin ; production designer, Bruton Jones.
Jon Foster, Sophia Bush, Frankie Muniz, Samaire Armstrong, Jimmi Simpson.
Unrated; for horror violence, disturbing images, language, brief sexual and drug content.
VCD
Keywords: Video games -- Drama; Teenagers and death -- Drama; Friendship -- Drama